Separation of zinc, cadmium and nickel from ZnO-CdO-NiO mixture through baking with ammonium chloride and leaching - Turan, M. Deniz; Safarzadeh, M. Sadegh (Elsevier Science Bv, 2012)
As part of a continuing effort, the separation of cadmium. nickel and zinc from ZnO-CdO-NiO mixture has been addressed to simulate the conditions encountered in Cd-Ni zinc plant purification residues. For this purpose, mixtures of ZnO, CdO, and NiO were baked at fairly low temperatures (200-400 degrees C) in the presence of ammonium chloride. As a result of baking, almost complete conversion of metals to their corresponding chlorides was achieved. While baking process provided no selectivity of metals, the subsequent water leaching process was successfully employed for the selective separation of metals based on leaching at different pH values. A factorial design of experiments was used to examine the main effects of the experimental parameters on the response. The proposed model fitted well to the experimental data according to R-2 and R-adj(2) correlation coefficients of response values. This procedure enabled the selective separation and concentration of zinc from the mixture. Ammonium chloride baking and leaching of a Cd-Ni zinc plant purification residue sample under similar conditions resulted in 88.1% Ni, 96.7% Cd, and less than 1% Zn extractions, showing a good agreement with the experimental results obtained from pure oxide mixtures. The findings of this research appear to be useful for the treatment of Cd-Ni zinc plant purification residues. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Nickel; Cadmium; Zinc; Ammonium chloride; Cd-Ni purification residues